Biopolymers Production by Mixed Culture and Their Applications in Water and Wastewater Treatment. (1st June 2015) - More, Tanaji T.; Yan, Song; Tyagi, Rajeshwar Dayal; Surampalli, Rao Y.
ABSTRACT: : Thirteen extracellular polymeric substances (EPS) producing bacterial strains were cultivated (as pure/mixed culture) in sterilized sludge (suspended solids: 25 g/L). The mixed culture produced higher concentrations of EPS (4.9 g/L) as compared to that of the pure culture (2.7–3.7 g/L). The harvested EPS were examined for their flocculation performance (turbidity removal and dewatering) in jar tests using kaolin suspensions with Ca 2+ . Broth (B‐EPS) revealed high kaolin flocculating activity (91.2%) at very low concentrations (0.8 mg B‐EPS/g kaolin) and it was comparable to the chemical polymer, Magnafloc‐155 (90.4% at 0.2 mg/g kaolin). B‐EPS also exhibited very good flocculation performance (turbidity removal %) in river water (93.5%), municipal wastewater (91.7%) and brewery wastewater (81.8%). The study revealed that the mixed culture consortium could be used for the production of highly efficient flocculants.